The impact of time spent working from home on affective commitment in the workplace: The mediating role of social relationships and collective aims - Simon, Adél Csenge; Aranyi, Gabor; Faragó, Klára; Pachner, Orsolya Csilla; Kiss, Orhidea Edith (Frontiers in Psychology, 2023)
Introduction Working from home has become increasingly prevalent due to the COVID-19 pandemic, creating new challenges for organizations and employees. According to the latent deprivation model proposed by Jahoda, work provides latent benefits alongside its material rewards, and losing such benefits leads to a decline in well-being. Organizational affective commitment, or affective commitment within the organization, is a prominent concept in organizational psychology that is linked to lower workforce fluctuation and increased work performance. The present research examined the impact of time spent working from home on affective commitment by examining Jahoda’s “latent functions,” including social contact and collective purpose, representing an innovative application of the latent deprivation model in the context of home office. Methods Using an online questionnaire, we collected data from 456 participants (239 female and 217 male) who had been employed for at least 2 years and who had spent a proportion of their time working from home in March and April 2021. The data were analyzed using a path model, in which the potential adverse effect of time spent in home office on affective commitment to the workplace was mitigated by latent functions. Results Specifically, we found that more time spent in home office was associated with a decrease in social contact, the impact of which on affective commitment was mediated through the perception of collective purpose. Discussion Our findings emphasize the role of the latent benefits of work experienced by employees even when working from home, and the role of those benefits in supporting employees’ commitment to the workplace. We argue that a deeper understanding of such factors is vital, as working from home is expected to remain widespread even after the pandemic.